Development and Validation of a Comprehensive Model for Diabetes Management in Iran - Farshad Falahati; Khalil Alimohammadzadeh; Seyed Mojtaba Hosseini; Ali Maher; Mehrnoosh Jafari (International Journal of Nutrition Sciences)
Background: Diabetes is still a significant global health challenge and it is estimated that 9.2 million Iranians by 2030 to suffer from the disease. Effective management is critical to reduce complications, costs, and improve quality of life, yet Iran’s care delivery system lags behind international standards. This study aimed to develop and validate acomprehensive model for diabetes management in Iran, tailored to its socio-economic context.Methods: A mixed-method approach was employed in four stages of (i) literature review to identify factors affecting diabetes management, (ii) qualitative interviews with 20 experts to extract key components, (iii) Delphi method to prioritize factors and (iv) the exploratory factor analysis (EFA) with 400 specialists to validate the model. Content validity (CVI≥0.79, CVR≥0.42) and reliability (Cronbach’s alpha=0.898) were assessed, with EFA confirming model fit (KMO=0.885, p<0.001).Results: Five key components were identified including leadership, management information, financial resources, human resources, and medical technologies. These were validated as critical ones for effective diabetes management, emphasizing team-based leadership, staff empowerment, sustainable financing, and robust training systems.Conclusion: The validated model offers a practical framework to enhance diabetes care in Iran that aligns with international standards and addresses local challenges. The strengthening leadership, investing in human resources, securing financial support, and leveraging technology are recommended in this relation. Future researches should be undertaken to validate the model across diverse regions and incorporate patient perspectives too.